Differences in the dynamic balance function of healthy elementary school students and university students observed with and without the use of a sensor-integrated gamification application - Kusumoto, Yasuaki; Ohmatsu, Satoko; Takahashi, Eri; Nakamura, Kanako (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveThis study examined differences in the dynamic balance function of healthy elementary school students and university students observed with and without the use of a sensor-integrated gamification application developed for pediatric rehabilitation.MethodsThis cross-sectional study was conducted between January and June 2025. and included a total of 79 participants (43 healthy elementary school students from Fukuoka, Japan; 36 healthy university students from Fukushima, Japan). Measurements were performed using a normal Y-Balance test and a Y-Balance test with a sensor game to encourage slow movements. The sensor sensitivity was set to 0.768 g and 7.53 m/s2 during game play.ResultsDuring the Y-Balance test, all items exhibited no significant interaction effects; however, several outcome measures exhibited main effects. The results of multiple comparison tests indicated different responses between groups attributable to sensor game use. No significant differences in the Y-Balance test items with or without the use of the sensor game for the dominant and non-dominant legs were observed in the university student group. Conversely, in the elementary school student group, the posterolateral scores of the Y-Balance test with the sensor game were significantly lower than those of the normal Y-Balance test.ConclusionThe sensor-integrated gamification application effectively increased task difficulty for healthy elementary school students by encouraging slower movements, leading to decreased dynamic balance function. This effect was not observed among university students. These findings suggest that sensor games may be valuable because they can appropriately adjust the difficulty level of balance exercises among elementary school students in rehabilitation settings.